2014
DOI: 10.2514/1.c032438
|View full text |Cite
|
Sign up to set email alerts
|

Fifth Drag Prediction Workshop: ONERA Investigations with Experimental Wing Twist and Laminarity

Abstract: This article is aimed at presenting the computational studies which have been performed at ONERA in 2013 in the framework of the 5 th AIAA Drag Prediction Workshop (DPW-5). As data concerning the Common Research Model (CRM) configuration was collected from the NASA Langley and Ames wind tunnels, a significant discrepancy appeared between the experimental and computational pitching moment evaluations. Investigations carried out by NASA in 2012 showed that the experimental model and the numerical geometry were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 14 publications
4
33
0
Order By: Relevance
“…Nevertheless, these differences are very limited in amplitude. In [26], it can be seen that the difference of wing twist values between the experimental and numerical models reveals much more significant discrepancies on pressure distributions at wingtip than what is shown in Fig. 27.…”
Section: Local Insightsmentioning
confidence: 67%
See 3 more Smart Citations
“…Nevertheless, these differences are very limited in amplitude. In [26], it can be seen that the difference of wing twist values between the experimental and numerical models reveals much more significant discrepancies on pressure distributions at wingtip than what is shown in Fig. 27.…”
Section: Local Insightsmentioning
confidence: 67%
“…Furthermore, in the experiments, laminar zones were present up to 10% chord whereas the CFD calculations are fully turbulent. These two differences impact the agreement that can be achieved (nevertheless it happens that they almost compensate each other [26]). Finally, the closest reference data that can be used for this paper corresponds to the numerical results obtained with the DPW-5 common grids described above.…”
Section: Reference Grids and Datamentioning
confidence: 89%
See 2 more Smart Citations
“…Additionally, the investigations of Rivers et al [15] also led to the discovery of a large discrepancy between the as-built and tested wind-tunnel model wing twist and the DPW-IV computational wing twist. Hue [16] showed that including the experimentally measured twist distribution reduced lift and improved the comparison with wind-tunnel measurements. Keye et al [17] also applied fluid-structure coupling and confirmed the shift in predicted forces and moments due to wing twist.…”
Section: Common Research Modelmentioning
confidence: 99%